(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Advancements in technology creates a new work environment and leads to many changes from developing new job roles to mass unemployment. However, for the present study the positive effects of technology are reviewed. Transfer of technological knowledge is crucial in developing the workforce and organization as a whole. This paper attempts to study the challenges to technological adoption. The paper is distributed into different sections analyzing the impacts and changes caused due to development in technology in labour markets, CSR (Corporate Socal Responsibility) activities, innovation and providing competitive advantage to the organizations. A conceptual model is developed based on the literature reviewed which brings out the various aspects that link technology advancement and its impacts in creating technological social responsibility. Further areas of study in this field are also suggested.